THE IMPACT OF MARKET EVOLUTION OF ARGAN OIL ON MOROCCAN ARGANERAIE - FAOUZI, Hassan (2016)
The argan tree (Argania spinosa (L) Skeels) is an endemic tree from Morocco that is used to feed people and animals. Argan oil is the most famous and most valued product of the argan tree due to its growing attractiveness. Prized by the industries of luxury cosmetic products and pharmaceutical products and by chefs, it is certainly one of the local resources of southern regions which has had a remarkably commercial growth in the last years. But in the southwestern region of Morocco, argan stands are steadily decreasing and regeneration is thus compromised. For fifteen years, efforts have been made to define the conditions for a truly sustainable development of the Moroccan arganeraies. Argan oil, produced from the edible oil from the argan fruit (affiache), is certainly the production which could be the basis for a socio-economic development project. Based on its success, argan oil has flooded the market of cosmetic products in Europe and North America in just a decade. However, a few years later, it has been verified that the commercial development of the “argan oil” industry has not had real effects on the preservation of argan forests, thus threatening this tree and its already weakened ecosystem.